Trends of the sufficient cadavers for human gross anatomy study at Naresuan University. - Chantapanit, R.; Chanasong, R.; Kumchantuek, T.; Putiwat, P.; Sakulsak, N. (Chulalongkorn Medical Journal, 2023)
Background : The Body Donation Unit, Department of Anatomy, Faculty of Medical Science, Naresuan University has been established for preparing cadavers for the teaching of human gross anatomy. Objective : To provide database for future management the number of cadavers for at least 5 years. Method : We retrospectively investigated for 15 years (2001 - 2015), regarding the numbers of donors annually, cumulative numbers of donors, numbers of deceased donors and numbers of cadavers. All data were analyzed statistically using percentage and regression analysis. Results : The results showed that the total number of donors in 15 years was 24,476. Most of donors were female (60.88%) and 50.7% of them were in age range of 41 - 60 years old. The numbers of donors trended to increase every year; this has been increasing about 37.5 fold for 15 years. However, the number of deceased donors was 1,174 and 52.2% of them were in the age range of 61 - 80 years old. Then, the average of mortality rate was 2 - 6% per year. The ratio of the numbers of cumulative donors: cumulative deceased donors: cumulative numbers of cadavers was 30.6: 1.2: 1. According to this ratio, the predicted numbers of deceased donors for the next 5 years (2016 - 2020) should be 956 cases and the predicted numbers of cadavers for teaching would be 275 cases and about 28.77%. The predicted numbers of reserved cadavers would be 681 cases. Conclusion : This study provides the obvious information that the body donation unit in Naresuan University is able to provide the sufficient cadavers for future usual courses of human gross anatomy. Moreover, there are enough cadavers for other human gross anatomy courses in the future.